Preclinic Activity Test of Capsule of Natural Ingredients Extract Combination of Noni Fruit (Morinda citrifolia L.) and Papaya Leaf (Carica papaya L.) as Hepatoprotector Agent for Tuberculosis (TB) Treatment - Ilham Kuncahyo; Supriyadi Supriyadi (Jurnal Farmasi Indonesia, 2014)
Research has been conducted in year 1st with the manufacture capsule of noni fruit (Morinda citrifolia L.) and papaya leaf (Carica papaya L.) as the active material to cope with damage to the liver (hepatoprotective) for the treatment of tuberculosis (TB). Year 2nd pre-clinical tests have been conducted using rats as test animals given INH and rifampicin that are often used in the treatment of tuberculosis for 28 days. Test animals consisted of 30 rats were grouped into six groups. Group I (normal control) were without any treatment, rat were given only the usual food and drink. Group II (negative control) were given INH-rifampicin suspension (INH dose of 10 mg/200 g BW and rifampicin dose of 10 mg/200 g BW. Group III (positive control) were given INH-rifampicin suspension and drug antihepatotoxic methicolÂ®. Group IV were given formula capsule 1, group V were given formula capsule 2, and group VI were given formula capsule 3. Parameters of liver damage was observed by measuring the levels of serum bilirubin, ALT and AST values. The parameters were measured on day 0 (before treatment), day 14, day 21, and day 28. There were observed liver histologically by histological methods-microscopic photograph using hematoxylin eosin staining. The data obtained were statistically evaluated using ANOVA one way for percentage of liver necrosis and two-way ANOVA for ALT, AST and serum bilirubin, with a 95% confidence level. The results showed that the formula capsule 1 of extract combination of papaya leaf and noni fruit with PVP binder 1 % was able to provide reduced liver damage on rats induced isoniazidrifampicin which was better than formula capsule 2 and 3.